Can peer education improve beliefs, knowledge, motivation and intention to engage in falls prevention amongst community-dwelling older adults? - Khong, L.; Berlach, R.; Hill, Keith; Hill, A. (Springer Verlag, 2017)
The aim of the study was to evaluate the effectiveness of delivering a contemporary peer-led falls prevention education presentation on community-dwelling older adults’ beliefs, knowledge, motivation and intention to engage in falls prevention strategies. A two-group quasi-experimental pre-test–post-test study using a convenience sample was conducted. A new falls prevention training package for peer educators was developed, drawing on contemporary adult learning and behaviour change principles. A 1-h presentation was delivered to community-dwelling older adults by peer educators trained with the new package (intervention group). Control group participants received an existing, 1-h falls prevention presentation by trained peer educators who had not received the adult learning and behaviour change training. Participants in both groups completed a purpose-developed questionnaire at pre-presentation, immediately post-presentation and at one-month follow-up. Participants’ levels of beliefs, knowledge, motivation and intention were compared across these three points of time. Generalised estimating equations models examined associations in the quantitative data, while deductive content analysis was used for qualitative data. Participants (control n = 99; intervention n = 133) in both groups showed significantly increased levels of beliefs and knowledge about falls prevention, and intention to engage in falls prevention strategies over time compared to baseline. The intervention group was significantly more likely to report a clear action plan to undertake falls prevention strategies compared to the control group. Peer-led falls prevention education is an effective approach for raising older adults’ beliefs, knowledge and intention to engage in falls prevention strategies.